Evaluación de la fertilización tradicional y la fertirrigación, en el cultivo de tomate de mesa (lycopersicon esculentum mill) bajo invernadero - Cabrera Flores, Jorge Iván (2017)
VIII. SUMMARY This research aims at evaluating the traditional fertilization and fertigation in tomato cultivation table (Lycopersicon esculentum) in greenhouse, located in the community San José Region Pimampiro province of Imbabura, this work was performed with the to evaluate the agronomic performance of the tomato crop to traditional fertilization and fertigation, identify the best method of traditional fertilization or fertigation and economically analyze treatments. Seven treatments by combining two types of fertilization and three doses of fertilizer and a control without application was investigated. The Complete Random Design (DCA) was used factorial arrangement A x B + 1 with 7 treatments and three repetitions, totaling 21 experimental units. The total area of the experiment was 688.00 m2, 23.40 m2 experimental plots. It was evaluated, electrical conductivity (C.E.). Potential hydrogen (pH). plant height, stem diameter, height insertion cluster first category of fruits, number of fruits per category, performance categories. The results determined that the cultivation of tomato variety Charleston, responded positively to the type of fertigation fertilization regarding stem diameter, number of fruits in first class, top-notch performance, the NPK Dosage (kg/ha): 71-58 -93: responded significantly in variables, number of fruit in first class, top-notch performance, the best combination in the agronomic performance and yield of tomato crop was fertilization Fertigation at doses of 71-58-93 (NPK) which reached greater stem diameter, number of fruits in first class and first class performance and higher net income of USD 38,671.96 and 36,460.83 / ha in tomato table it was obtained with the application through fertigation 145-115-185 and dose of 71-58-93 (NPK)